IMPLEMENTATION IMPACT OF THE TRIPLECHEM LEARNING MODEL ON PERSONAL AND SOCIAL ATTITUDES OF CHEMISTRY PROSPECTIVE TEACHERS - suja, wayan (LPPM Undiksha, 2017)
This study was aimed at describing and explaining the impact of the application of TripleChem learning model to the personal and social attitude of chemistry prospective teacher. The study was conducted in three classes of Organic Chemistry I at the Chemistry Education Department of Universitas Pendidikan Ganesha in the odd semester of the 2015/2016 academic year. Each class consists of 22 students. In each class, learning is done by applying the TripleChem learning model. The data were collected by two observers using the observation sheet. Data analysis was performed descriptively. The results indicate that the personal and social attitudes of prospective teachers have increased gradually until it reaches the optimum condition around the eight meeting. The findings suggest that the TripleCem learning model is effectively implemented to train the personal and social attitudes of chemistry prospective teachers.